2014
DOI: 10.1007/s12288-014-0374-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Identification of Platelet-Associated Alloantibodies by a Solid-Phase Modified Antigen Capture Elisa (MACE) Technique and Its Correlation to Platelet Refractoriness in Multi platelet Concentrate Transfused Patients

Abstract: Platelets express glycoproteins (IIb/IIIa, Ib/IX, Ia/IIa, IV, and HLA-1) that are polymorphic and can become targets for antibody responses. Patients at threat are those who received multiple platelet transfusions. Modified antigen capture elisa (MACE) is a qualitative solid phase Elisa designed to detect IgG antibodies against platelet specific antigens. The study has been carried out over a period of 2 years. A total of 100 patients were selected, who had been transfused with at least 15 units of platelet co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
5
1
1
Order By: Relevance
“…It must also be added that we could not trace the gender of the source of the transfused platelet transfusions. Although previous studies reported an increase in the frequency of alloimmunization as the number of transfusions increases, 6 we failed to confirm these observations in our cohort. The wide prevalence of platelet alloimmunization in multi-transfused patients obtained in this study along with its possible clinical consequences, especially refractoriness to platelet transfusion and its close association with patient survival, 18 emphasizes the importance of pre-transfusion platelet antibody screening of such patients as well as the establishment of stocks of HPAs and HLA typed platelet units of platelet concentrate, so that the needy patients should receive units that lack any antigens corresponding to the antibodies detected in their blood.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…It must also be added that we could not trace the gender of the source of the transfused platelet transfusions. Although previous studies reported an increase in the frequency of alloimmunization as the number of transfusions increases, 6 we failed to confirm these observations in our cohort. The wide prevalence of platelet alloimmunization in multi-transfused patients obtained in this study along with its possible clinical consequences, especially refractoriness to platelet transfusion and its close association with patient survival, 18 emphasizes the importance of pre-transfusion platelet antibody screening of such patients as well as the establishment of stocks of HPAs and HLA typed platelet units of platelet concentrate, so that the needy patients should receive units that lack any antigens corresponding to the antibodies detected in their blood.…”
Section: Discussioncontrasting
confidence: 96%
“… 4 In hemato-oncology patients receiving multiple transfusions, the production of these antiplatelet antibodies will result in shortening the survival of donated platelets and render the patient refractory to platelet transfusions. 5 , 6 Information on these areas is lacking in our population and, in view of the genetic variations that exist within and between ethnic groups and the current practice of random selection and transfusion of platelet products, it is of interest to find out the extent of alloimmunization to these antigens. Therefore, the main aim of this study is to determine the frequency of antibodies to HPAs and HLA1 in multiparous women and multi-transfused patients from Saudi Arabia.…”
mentioning
confidence: 99%
“…An unexpected finding made in our previous studies 1 was that nearly all mice immunized intraperitoneally or intravenously with platelets from one of the other three strains produced GPIIb/IIIa‐specific alloantibodies, despite the relatively small numbers of AA differences in extracellular domains of GPIIb/IIIa in these strains (Table 1). This behavior contrasts markedly with experience in humans transfused with whole blood or platelets in whom alloantibodies against platelet‐specific GPs (HPA antibodies) are relatively uncommon 18–21 but who often become immunized against Class I HLA antigens and may become refractory to randomly selected platelet transfusions as a consequence 18,22–24 . Interstrain platelet transfusions in mice have been used to model antibody‐dependent platelet transfusion refractoriness that develops in multiply transfused human patients, characterize its pathogenesis and examine ways that this complication can be circumvented 25–30 .…”
Section: Discussionmentioning
confidence: 99%
“…The antiplatelet antibody bound to the GP is detected by the addition of a peroxidase-labeled anti-human IgG, followed by an appropriate substrate. 64 (b) Modified antigen capture Elisa assay: Platelets are incubated with antiplatelet antibodies, and then lysed. The complex consisting of GPs/antiplatelet antibody is added to the well of a microtiter plate coated with specific monoclonal antibody that capture the complex, and the captured complex is detected by the addition first of a peroxidase-labeled anti-human IgG and then an appropriate substrate.…”
Section: Antigen Capture Assaysmentioning
confidence: 99%